Magnetic classification in wet-mode: Proofs of concept, and applications - barbosa, d (2019)
We have developed recently an indirect proof of concept (POC) of magnetic classification in wet mode. This POC, was accompanied by another one, concerning fundamental background theory and simulations. Both POC's proved the feasibility of the process and specially have allowed to determine the influence of some of the force balances and some of the main parameters in fluid media. Based on the preliminary results we are now ready to develop, design and control a larger scale device for future applications, and to strength the proof of concept by direct determination. Bearing in mind the systems and trajectories obtained we were able to conclude that magnetic classification was able to be achieved with the classes differences shown in Table 1. Developing this processing techniques allow us to selectively separate and purify several substances at the same step and in the same device, especially in what concerns biomedical applications (ranging from diagnostics until treatment of diseases), mineral processing, water treatment and recycling, as modern technologies are still very limited regarding this goal. The main applications and the improved given by magnetic classification will be also detailed.